Prehod iz običajne v zelo hitro obdelavo in analiza oblikovanja odrezkov - Ekinović, Sabahudin (Strojniški vestnik, 2002)
As a result of advances in machine-tool design(main, spindle, feed drives, etc.), high-speed milling has become a cost-effective manufacturing process for making products with a high surface quality, low variations of the machined surface and excellent dimensional accuracy. Taking into account the evident advantages of high-speed machining over conventional machining, a key issue is to identify those cutting speeds that correspond to high-speed machining. The simple reason for this is that machining effects increase when entering the high-speed region but , on the other hand, an enormous increase in the cutting speed is not advisible due to the appearance of higher tool wear and machine-tool energy consumption. In order to solve the problem this paper describes a procedure based on a chip-formation mechanism and a chip-shape analysis, together with the use of metallographic methods.
Keywords: stroji obdelovalni; obdelave visokohitrostne; oblike-odrezkov; hitrosti rezanja; visokohitrostna obdelava; odrezovanje; frezanje; odrezki